A human telomeric G-quadruplex-based electronic nanoswitch for the detection of anticancer drugs1. Issue 12 (21st June 2015) - Bagheryan, Zahra; Raoof, Jahan-Bakhsh; Ojani, Reza; Rezaei, Parizad
<x xml:space="preserve">Abstract</x> A nanoswitch for the detection of anticancer drugs based on G-quadruplex structure.